2003
DOI: 10.1038/sj.cr.7290147
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of swelling-activated chloride channels in embryonic chick heart cells

Abstract: Swelling-activated Cl − currents, I (Cl,swell) , were measured during hyposmotic shock in white Leghorn embryonic chick heart cells using the whole-cell recording of patch-clamp technique. Genistein, an inhibitor of protein tyrosine kinase (PTK), suppressed I (Cl,swell) . Under isosmotic condition phorbol 12-myristate 13-acetate (PMA), an activator of PKC, elicited the Cl − current similar to that in hyposmotic solution, whereas hyposmotic shock did not elicit I (Cl,swell) in chelerythrine chloride(an inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Similar downregulating effects of PKC activators have been observed for native VSOR Cl -currents recorded not only from rabbit and guinea pig cardiomyocytes [39,46] but also from other cell types [29,[47][48][49][50][51][52][53][54]. In contrast, the activity of VSOR Cl -channels in canine and chick cardiomyocytes [55,56], and many epithelial cells [57][58][59][60], has been reported to be enhanced by PKC activation. It is noteworthy that such opposite PKC dependency of native VSOR Cl -currents has been observed even in cells where ClC-3 is expressed [39,46,48,50,51,53,55,57].…”
Section: Discussionmentioning
confidence: 87%
“…Similar downregulating effects of PKC activators have been observed for native VSOR Cl -currents recorded not only from rabbit and guinea pig cardiomyocytes [39,46] but also from other cell types [29,[47][48][49][50][51][52][53][54]. In contrast, the activity of VSOR Cl -channels in canine and chick cardiomyocytes [55,56], and many epithelial cells [57][58][59][60], has been reported to be enhanced by PKC activation. It is noteworthy that such opposite PKC dependency of native VSOR Cl -currents has been observed even in cells where ClC-3 is expressed [39,46,48,50,51,53,55,57].…”
Section: Discussionmentioning
confidence: 87%
“…What is the mechanism by which tamoxifen inhibits I Cl,vol ? It has been revealed that protein kinase C (PKC) was involved in the activation of I Cl,vol (Shuba et al, 1996; Wei et al, 2003) and tamoxifen showed an inhibitory effects of on PKC (Horgan et al, 1986; Kuo et al, 2011). Would tamoxifen suppress I Cl,vol by inhibiting PKC?…”
Section: Resultsmentioning
confidence: 99%
“…Tamoxifen has been found to inhibit PKC activity for long time (O'Brian et al, 1985; Ramachandran et al, 2004). Down regulation of PKC activity could downregulate (Chou et al, 1998; Wei et al, 2003), upregulate (Shi et al, 2002; Xiong et al, 2009), or not affect I Cl,vol (Szucs et al, 1996; Leaney et al, 1997) in different cell lines. Is PKC involved in the inhibitory effect of tamoxifen on I Cl,vol in MHCC97H cells?…”
Section: Discussionmentioning
confidence: 99%
“…I Cl,swell activated by mechanical stretch of rabbit ventricular myocytes is suppressed by acute application of either genistein or PP2 (7). On the other hand, genistein and PP2 stimulate swelling-induced I Cl,swell in human atrial myocytes (15), but genistein inhibits I Cl,swell in cultured embryonic chick heart (56). Thus the regulation of I Cl,swell is likely to depend on the method of stimulation (e.g., swelling vs. stretch) and the particular tissue studied.…”
Section: Discussionmentioning
confidence: 99%